2021
DOI: 10.1002/hyp.14199
|View full text |Cite
|
Sign up to set email alerts
|

How realistic are water‐balance closure assumptions? A demonstration from the southern sierra critical zone observatory and kings river experimental watersheds

Abstract: The water balance is an essential tool for hydrologic studies and quantifying waterbalance components is the focus of many research catchments. A fundamental question remains regarding the appropriateness of water-balance closure assumptions when not all components are available. In this study, we leverage in-situ measurements of water fluxes and storage from the Southern Sierra Critical Zone Observatory (SSCZO) and the Kings River Experimental Watersheds (KREW) to investigate annual water-balance closure erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 70 publications
3
35
0
Order By: Relevance
“…The combined result of these advances indicated widespread non-zero G + 𝐴𝐴 𝐴𝐴 in a range of upland settings: for example, inferred groundwater behavior (i.e., G + 𝐴𝐴 𝐴𝐴 ) as determined by the evaluation of Equation 2 using TC-Merged P & ET suggested that 85 of 114 upland catchments were not self-contained. These findings provide broad and quantitative evidence in support of recent calls to revisit common assumptions about G and 𝐴𝐴 𝐴𝐴 used to close the water budget and derive 𝐴𝐴 𝐴𝐴𝐴𝐴CWB in upland settings (Fan, 2019;Kampf et al, 2020;Safeeq et al, 2021). At the same time, our results point to the very real challenge of disentangling signal associated with G from 𝐴𝐴 𝐴𝐴 (Figures 3 and 5, Tables 4-6) in upland settings that lack comprehensive groundwater datasets (Fan, 2019) and are more susceptible to the systematic under-prediction of P (Lundquist et al, 2019;Rasmussen et al, 2012;Wrzesien et al, 2019).…”
Section: Budyko Q Anom Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The combined result of these advances indicated widespread non-zero G + 𝐴𝐴 𝐴𝐴 in a range of upland settings: for example, inferred groundwater behavior (i.e., G + 𝐴𝐴 𝐴𝐴 ) as determined by the evaluation of Equation 2 using TC-Merged P & ET suggested that 85 of 114 upland catchments were not self-contained. These findings provide broad and quantitative evidence in support of recent calls to revisit common assumptions about G and 𝐴𝐴 𝐴𝐴 used to close the water budget and derive 𝐴𝐴 𝐴𝐴𝐴𝐴CWB in upland settings (Fan, 2019;Kampf et al, 2020;Safeeq et al, 2021). At the same time, our results point to the very real challenge of disentangling signal associated with G from 𝐴𝐴 𝐴𝐴 (Figures 3 and 5, Tables 4-6) in upland settings that lack comprehensive groundwater datasets (Fan, 2019) and are more susceptible to the systematic under-prediction of P (Lundquist et al, 2019;Rasmussen et al, 2012;Wrzesien et al, 2019).…”
Section: Budyko Q Anom Resultssupporting
confidence: 68%
“…particularly biases (i.e., systematic error) in estimates of precipitation (P) associated with complex topography and snow plague water balance closure in upland catchments (Bales et al, 2006;Carroll et al, 2019;Henn et al, 2018). To circumvent these challenges, conventional approaches often assume that unknown or uncertain variables (including error) can be ignored by imposing a closed water budget (CWB, Fan, 2019;Kampf et al, 2020;Safeeq et al, 2021). To illustrate this point, we present a simple, but complete, catchment water budget following Fan (2019):…”
mentioning
confidence: 99%
“…Valley shape can control groundwater recharge, where wider, flatter valley bottoms facilitate more deep groundwater recharge than steep, narrow valleys (Prancevic & Kirchner, 2019). This deep groundwater recharge may constitute a net loss of water from some mountain headwater catchments (Safeeq et al, 2021). Another explanation could be that the denser vegetation at Michigan River transpired more water than at Andrews Creek, where a larger fraction of area was covered with exposed bedrock.…”
Section: Discussionmentioning
confidence: 99%
“…Safeeq et al. (2021), when investigating the water balance closure assumptions of six river basins (>1,000 km 2 ) and 10 headwater catchments (<5 km 2 ) in the southern Sierra Nevada, found IGF higher than the typical amount of measurement bias for both evaluated spatial scales, arguing for a greater consideration of IGF when evaluating hydrological processes, especially for small spatial scales.…”
Section: Introductionmentioning
confidence: 99%